2009
DOI: 10.1111/j.1464-5491.2009.02737.x
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s national trends in the incidence of Type 1 diabetes in 0–14‐year‐olds, 2000–2006

Abstract: The incidence of Type 1 diabetes among 0-14-year-olds in Australia is very high compared with available data from many other countries. The rate of increase observed globally in the last decade has continued well into this decade in Australia. The rising incidence cannot be explained by changes in genetic susceptibility; there is an urgent need to examine the environmental factors that have contributed to this increase. The findings of this study also have important implications for resource planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 22 publications
5
39
1
2
Order By: Relevance
“…The UE-IR of T1DM girls was higher than that of boys over a period of 16 years, which is consistent with our findings in the period of 1988-1996 [5] and international research data [15,16]. Some studies found no differences between genders [17,18,19] or the incidence in boys was higher than that in girls [20,21]. A high incidence in diabetes in girls may be one of the features of T1DM in China.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The UE-IR of T1DM girls was higher than that of boys over a period of 16 years, which is consistent with our findings in the period of 1988-1996 [5] and international research data [15,16]. Some studies found no differences between genders [17,18,19] or the incidence in boys was higher than that in girls [20,21]. A high incidence in diabetes in girls may be one of the features of T1DM in China.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were reported in several countries, both high-incidence countries such as Finland [24], Sweden [25], America [26], Canada [27], Australia [20] and low-incidence countries such as Austria [28 ]and Poland [29]. These studies also have reported an accelerated increase in the incidence in children less than 5 years old [1,4].…”
Section: Discussionsupporting
confidence: 72%
“…For the last 15 years, an almost threefold increase in the incidence of type 1 diabetes mellitus (T1DM) in children and adolescents has been observed in Poland and a further at least fourfold increase is expected by 2025 [1][2][3]. Therefore, the number of patients with vascular complications is also increasing [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Nas Américas, o número de pessoas com DM foi estimado em 3,5 milhões em 2000, e espera-se um aumento para 64 milhões em 2025 5 . Existe uma grande diferença na incidência do DM nas diversas regiões do mundo, que alcança grandes amplitudes de diferentes incidências, como 0,1/100.000 por ano na China e 45/100.000 por ano na Finlândia, 0,1/100.000 na Venezuela (Caracas) e 8/100.000 no Brasil (São Paulo) 4,6,7 . Em um dos centros participantes do Estudo Brasileiro de Incidência de Diabetes Mellitus Insulino-Dependente, que é componente do estudo Diabetes Mondiale (Projeto DIAMOND), foi verificada uma incidência média de 12,7/100.000 em Londrina (PR), que é superior à de 7,6/100.000 em São Paulo (SP) e bem superior à de 1,8/100.000 em Campina Grande (PB) 8 .…”
Section: Introductionunclassified